Multi-omics analysis reveals the mechanism for galactose metabolism in mutant Streptococcus thermophilus IMAU20551Y - Jiahui Tai; Haimin Hu; Jinhui Liu; Wenhui Lu; Tong Dan (Current Research in Food Science)
Streptococcus thermophilus (S. thermophilus) is a species widely used in the dairy industry to accelerate the acidification rate and improve the texture and flavour characteristics of dairy products. However, most S. thermophilus have galactose-negative (Gal−) phenotypes, which can lead to accumulation of free galactose in fermented dairy products. In a previous study, a mutant of S. thermophilus IMAU20551Y was obtained by N-methyl-N′-nitro-N-nitrosoguanidine (NTG) mutagenesis in which key enzymes related to galactose metabolism were significantly changed compared with the wild type. β-galactosidase and galactokinase activity were higher in the mutant while glucokinase and pyruvate kinase activities were significantly decreased compared with the wild type. In this study, the ability of the mutant to metabolize galactose was verified by high performance liquid chromatography (HPLC), and the mechanism for enhanced galactose metabolism elucidated by multi-omics analysis. HPLC analysis showed that accumulation of galactose in milk fermented by mutant S. thermophilus IMAU20551Y was reduced by 41.4%, compared with the wild type. Although no mutations in gene sequences associated with galactose metabolism were detected by genome sequencing, transcriptomic data showed up-regulation in expression of galM, galK, galT, galE (associated with the Leloir pathway) and LacI family transcriptional regulator GalR, resulting in enhanced galactose metabolism in the mutant. This study provides a reference for genetic engineering modification of galactose-positive (Gal+) S. thermophilus, which is expected to be used as a starter for the production of low galactose fermented dairy products.